'Nae too bad': job satisfaction and staff morale in Scottish residential child care - Andrew Kendrick; Ian Milligan; Ghizala Avan (Scottish Journal of Residential Child Care)
In 2003, the National Children's Bureau and the Social Education Trust published a report - Better Than You Think -on staff morale, qualifications and retention in residential child care in England (Mainey, 2003a; Mainey,2003b). It found that levels of morale and job satisfaction were not low despite the adverse environment in which residential care operates. Residential care in the modern world is intended to be mainly a temporary placement for some of the most demanding young people who need to be looked after and accommodated. The sector also continues to struggle with the aftermath of a number of high profile public inquiries of the abuse of children and young people in residential care (Kent, 1997; Marshall, Jamieson & Finlayson, 1999; Utting, 1997; Waterhouse, 2000). Residential child care in Scotland is under pressure to improve standards of care in a climate of negative media attention and public suspicion. It was in this context that the Social Education Trust funded a parallel study of job satisfaction and staff morale in Scotland (Milligan, Kendrick & Avan, 2004).